Strategi dan Manajemen Pengembangan Sumber Daya Manusia Pada UMKM Masyarakat : Studi Kasus RW017, RW018, dan RW008 Perumahan Benda Baru Pamulang, Tengerang Selatan, Banten - Salsabila Esa Utami; Delsa Yunia Permatasari; Anissa Salsabila; Nani Qurotul A’yun; Anjely Shukriya Aini (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
Human resource (HR) development is a crucial element in enhancing productivity and sustainability of micro, small, and medium enterprises. This study aims to identify the strategies and human resource management practices implemented in the MSMEs of the communities in RW017, RW018, and RW008 of Benda Baru Housing, Pamulang, South Tangerang, Banten. The method used is a qualitative approach with data collection techniques through interviews, observations, and document studies. The results show that skill-based training, business mentoring, and the introduction of digital technology are key strategies to improve HR competencies. Additionally, cooperation between the community, local government, and the private sector has a positive impact on access to financing and marketing networks. However, challenges such as limited resources, lack of managerial knowledge, and low digital literacy remain obstacles. This study recommends the strengthening of continuous training programs, integration of technology, and synergy among stakeholders to support holistic HR development. In this way, the community’s of micro, small, and medium enterprises can grow more optimally and contribute to the local economy.